If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) + -7x = 9(x + -18) + 9x + -2 Reorder the terms: 3(2 + x) + -7x = 9(x + -18) + 9x + -2 (2 * 3 + x * 3) + -7x = 9(x + -18) + 9x + -2 (6 + 3x) + -7x = 9(x + -18) + 9x + -2 Combine like terms: 3x + -7x = -4x 6 + -4x = 9(x + -18) + 9x + -2 Reorder the terms: 6 + -4x = 9(-18 + x) + 9x + -2 6 + -4x = (-18 * 9 + x * 9) + 9x + -2 6 + -4x = (-162 + 9x) + 9x + -2 Reorder the terms: 6 + -4x = -162 + -2 + 9x + 9x Combine like terms: -162 + -2 = -164 6 + -4x = -164 + 9x + 9x Combine like terms: 9x + 9x = 18x 6 + -4x = -164 + 18x Solving 6 + -4x = -164 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 6 + -4x + -18x = -164 + 18x + -18x Combine like terms: -4x + -18x = -22x 6 + -22x = -164 + 18x + -18x Combine like terms: 18x + -18x = 0 6 + -22x = -164 + 0 6 + -22x = -164 Add '-6' to each side of the equation. 6 + -6 + -22x = -164 + -6 Combine like terms: 6 + -6 = 0 0 + -22x = -164 + -6 -22x = -164 + -6 Combine like terms: -164 + -6 = -170 -22x = -170 Divide each side by '-22'. x = 7.727272727 Simplifying x = 7.727272727
| (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 | | 26-9x=10+7x | | -5x+15=-2x+3 | | 3a+4=6a-2 | | 2x^2+mx+3=x+1 | | f(x)=12+3x | | 12y+11=6y+41 | | 11y-6=93 | | 6(6-6n-3)+3=8n+29 | | 13+3p=7-3p | | 3(x+2)=7(x-2) | | 0.625y-7=-2 | | -5(r+6)=-84 | | 3+5b=3b-1 | | 2[-(x-1)+4]=5+[-(6-7)+9x] | | -7-8r=1-6r-4 | | 8x+7x-66=110-7x | | 3.9=-log(x) | | 4x^2-100=9 | | 2y+4x=c |